12-year continuous biochar application: Mitigating reactive nitrogen loss in paddy fields but without rice yield enhancement - Jin, Penghui; Chen, Zhe; Wang, Hui; Lv, Runjin; Hu, Tianlong; Zhou, Rong; Zhang, Jingru; Lin, Xingwu; Liu, Qi; Xie, Zubin (Agriculture, ecosystems & environment, 2024)
Numerous studies have documented the beneficial effects of short-term biochar application on soil carbon sequestration, greenhouse gas emissions reduction, and ecological functions enhancement. However, concerns persist regarding the impacts on soil reactive nitrogen (N) loss and crop yields under long-term biochar application (more than ten years), due to the irreversibility once biochar is incorporated into soils. This study presents the results of a 12-year field experiment in a rice-wheat rotation system with treatments including a control (CK, no corn straw or biochar), annual corn straw returning (CS, 6 Mg·ha−1·yr−1), and annual application of corn straw biochar pyrolyzed at 400°C at rates of 2.4, 6, and 12 Mg·ha−1·yr−1 (BC1, BC2, and BC3), investigating rice yields (2011–2022) and reactive N loss (2021–2022). The results showed that after 11 years of continuous biochar application until the 2021 rice season, alkaline hydrolysis N (AN, equivalent to an average of 347 kg N ha−1) within the 0–15 cm soil layer in biochar treatments was significantly higher than that of the CK (200 kg N ha−1), attributable to the biochar-induced enhancement of cation exchange capacity (CEC). The application of biochar reduced inorganic N leaching and NH3 volatilization losses by an average of 42.21 % and 30.85 %, respectively. However, N2O emission in the BC3 treatment was over 2 times as high as in the CK. Continuous biochar applications did not increase rice yield over the 12 rice seasons, as excessive soil AN level under biochar application reduced the rice harvest index. The results indicated that continuous biochar application was effective in reducing reactive N losses and increasing plant-available N supply, suggesting a potential to sustain rice production with lower fertilizer N inputs. [Display omitted] •BC increased soil alkaline hydrolysis N and cation exchange capacity.•Cumulative BC (26.4, 66 and 132 Mg·ha−1) raised soil pH by < 1 % on average.•BC reduced NH3 volatilization and inorganic N leaching but raised N2O emission.•BC reduced plant harvest index and N harvest index.•BC did not increase rice yield over 12 consecutive rice seasons.